Bioengineering a Human Face Graft: The Matrix of Identity. Issue 5 (November 2017) - Duisit, Jérôme; Maistriaux, Louis; Taddeo, Adriano; Orlando, Giuseppe; Joris, Virginie; Coche, Emmanuel; Behets, Catherine; Lerut, Jan; Dessy, Chantal; Cossu, Giulio; Vögelin, Esther; Rieben, Robert; et al.
Abstract : Objective: During the last decade, face allotransplantation has been shown to be a revolutionary reconstructive procedure for severe disfigurements. However, offer to patients remains limited due to lifelong immunosuppression. To move forward in the field, a new pathway in tissue engineering is proposed. Background: Our previously reported technique of matrix production of a porcine auricular subunit graft has been translated to a human face model. Methods: 5 partial and 1 total face grafts were procured from human fresh cadavers. After arterial cannulation, the specimens were perfused using a combined detergent/polar solvent decellularization protocol. Preservation of vascular patency was assessed by imaging, cell and antigen removal by DNA quantification and histology. The main extracellular matrix proteins and associated cytokines were evaluated. Lip scaffolds were cultivated with dermal, muscle progenitor and endothelial cells, either on discs or in a bioreactor. Results: Decellularization was successful in all facial grafts within 12 days revealing acellular scaffolds with full preservation of innate morphology. Imaging demonstrated a preservation of the entire vascular tree patency. Removal of cells and antigens was confirmed by reduction of DNA and antigen markers negativation. Microscopic evaluation revealed preservation of tissue structures as well as of major proteins. Seeded cells were viable and well distributed within all scaffolds. Conclusions: Complex acellular facial scaffolds were obtained, preserving simultaneously a cell-friendly extracellular matrix and a perfusable vascular tree. This step will enable further engineering of postmortem facial grafts, thereby offering new perspectives in composite tissue allotransplantation.